Analisis Potensi dan Pertumbuhan Ekonomi Daerah Kabupaten Solok - ,, Badri (LLDIKTI Wilayah X, 2014)
This study is intended to Article Labels analyze how Potential Large And Economic growth in Solok . The analysis tool which was used in this study is Quotients Label Klassen , Economy New Articles of Association analysis using calculations Quetiont Location ( LQ ) and Shift- Share analysis . The data used is secondary data New Articles From the analysis period of 2000-2009 , where TIN Data from the Central Statistics Agency ( BPS ) and the District of Solok of West Sumatra .Results show that the classified Solok district Astra Honda Motor as the area is Developing New Articles The High rate of economic growth , however Low per capita income than the provincial average - average West Sumatra . New Articles The Economic base analysis is measured by calculating the location Quetiont , shows that the sector - Potentially sector in Solok sector is Agriculture, Mining and quarrying sector As well as building sector. By THEREFORE , Dalam Frame improve economic growth and per capita income, Solok District Local Government therefore needs to increase the Seremban want to search ? New Articles swatch GDP increases the investment of the SIBOR ( in addition to English On the Government side ) .Keywords : Typology Klassen , Location Quetiont ( LQ ) , Shift- Share